IMPLEMENTASI SISTEM SMART DOORLOCK KOST BERBASIS ESP32 DENGAN DETEKSI STATUS TAGIHAN MENGGUNAKAN LOGISTIC REGRESSION DAN MONITORING APLIKASI MOBILE - Riski Virmansah; Indah Sulistiyowati; Jamaaluddin Jamaaluddin; Akhmad Ahfas (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2026)
The management of boarding houses (kost) is not only related to providing residential facilities, but also involves administrative payment management and access security for tenants. Common problems that frequently occur include late payment of rental fees and the use of conventional door locks, which are vulnerable to misuse such as key duplication and unauthorized access. These conditions make it difficult for boarding house owners to monitor payments and room access effectively and in real time. Therefore, this study aims to design and implement an ESP32-based smart boarding house door lock system integrated with RFID, Firebase, and a mobile application, complemented by billing status detection using the Logistic Regression algorithm. The system operates by reading the tenant’s RFID card as an access identifier. The tenant’s identity data is then verified through the Firebase database to determine the payment status. Door access is granted only to tenants with a confirmed paid status, while tenants with outstanding payments are automatically restricted from accessing the room. The Logistic Regression algorithm is applied to predict payment status based on historical payment data, such as the duration of arrears and the frequency of on-time payments. The research method used in this study is Research and Development (R&D), which includes problem identification, literature study, hardware and software design, system testing, and result analysis. The expected outcome of this research is to enhance room access security, simplify real-time payment monitoring for boarding house owners through a mobile application, and create a more efficient, practical, and integrated boarding house management system based on Internet of Things technology.